Gender, body and sport in historical and transnational perspectives - Bandy, Susan J. 1948- (Schriften zur Sportwissenschaft, 2008)
"In Gender, Body and Sport in Historical and Transnational Perspectives, honouring Gigliola Gori, nineteen European and North American scholars explore a variety of subjects including the influence of fascism on the arts, the Olympic Games, and intersections of the body, gender, and ideology in sport. This collection of original essays marks a shift from national to transnational perspectives in sport research, and many of the essays explore the way in which the forces of history fashioned the development of sport and the sporting lives of relatively unknown yet important figures in sport."--Publisher description.